Orin ori-oke': a thematic examination of songs used in Ikoyi prayer mountains, Osun State, Nigeria (2018)
Prayer Mountaineering is a dominant religious activity practised by Christians in Africa; it represents a culture of setting apart specific spaces such as groves, thick forests, hilly places and mountains, river hanks and so forth by African Indigenous Churches (AICs) for spiritual exercises. Prayer Mountains were peculiar places where founders of many AICs encountered divine interactions and over time have become places where a myriad of religious activities, including observance of prescribed period of seclusions, offering of special prayers and related activities take place. There is a proliferation of Prayer Mountains in Oyo, Osun and Ekiti states. While religious, social and economic activities of Prayer Mountains have received scholarly investigation, no known study has examined their musical activities. This study, therefore, investigates the musico-cultural practices taking place in Ikoyi Prayer Mountains, Osun State, Nigeria, using ethnographic research approach. It also identified thematic orientations and attendant dynamics embedded in the song texts. Songs were musically represented using Sibelius 7.5 music notation software and data subjected to content analysis.